Drug Treatment of Trichotillomania (Hair-Pulling Disorder), Excoriation (Skin-picking) Disorder, and Nail-biting (Onychophagia) - Sani, Gabriele; Gualtieri, Ida; Paolini, Marco; Bonanni, Luca; Spinazzola, Edoardo; Maggiora, Matteo; Pinzone, Vito; Brugnoli, Roberto; Angeletti, Gloria; Girardi, Paolo; Rapinesi, Chiara; Kotzalidis, Georgios D. (Current Neuropharmacology, 2019)
Background: Trichotillomania (TTM), excoriation (or skin-picking) disorder and some severe forms of onychophagia are classified under obsessive-compulsive and related disorders. There are different interacting neurotransmitter systems involved in the pathophysiology of impulse-control disorders, implicating noradrenaline, serotonin, dopamine, opioid peptides and glutamate, hence investigators focused on drugs able to act on these transmitters. Our aim was to critically review the efficacy of the drugs employed in impulse-control disorders. Methods: We searched for controlled drug trials to treat TTM, excoriation, and/or nail-biting six databases (PubMed, Cochrane, Scopus, CINAHL, PsycINFO/PsycARTICLES, and Web of Science), using the search strategy: (trichotillomania OR “excoriation disorder” OR “face picking” OR “skin picking” OR “hair pulling” OR onychophagia OR “nail-biting”) AND drug treatment on 12 March 2018 for all databases. We followed in our method of identifying relevant literature the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: SSRIs and clomipramine are considered first-line in TTM. In addition, family members of TTM patients are often affected by obsessive-compulsive spectrum disorders. Other drugs used in the treatment of TTM are lamotrigine, olanzapine, N-Acetylcysteine, inositol, and naltrexone. Conclusion: The treatment of TTM, excoriation disorder and nail-biting is still rather disappointing. Conjectures made from preclinical studies and the relative pathophysiological hypotheses found poor confirmations at a clinical level. There is a need for further studies and the integration of pharmacological and psychotherapeutic. Our results point to the need of integrating personalised medicine principles in the treatment of these patients.
Keywords: trichotillomania